2017
DOI: 10.1177/0886260517746944
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Consequences to Assisting Victims of Campus Violence: Initial Investigations Among College Students

Abstract: Despite growing interest in the use of bystander education programs to address the problems of sexual and relationship violence on college campuses, little knowledge exists on adverse consequences experienced by students intervening as a bystander. The current study examined the prevalence and correlates of adverse consequences of bystander intervention in two samples of first-year college students. In Study 1, 281 students completed a measure of negative consequences experienced when acting as a bystander to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…While most studies were operationalized as an experiment with participants incorporating a simulated VR environment, three studies were randomized controlled trials [20,30,35]. Different violent incident scenarios were used across these studies, including school bullying behaviors (including relational, verbal, and/or physical violence) among student peers [22,35]; sexual assault incidents that took place in dating or a potential dating relationship [20,21,35,36]; a combination of different types of assaults among friends or acquaintances [30]; and verbal and physical assaults that occurred among strangers [19,29,31,37]. In addition to the victim-aggressor relationship, we examined the relationship between victims and bystanders simulated in the VR scenarios, including school peers (n=2) [22,35], friends (n=5) [20,21,30,36,38], and strangers (n=4) [19,29,31,37].…”
Section: Review Results and Summary Of The Main Characteristics Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies were operationalized as an experiment with participants incorporating a simulated VR environment, three studies were randomized controlled trials [20,30,35]. Different violent incident scenarios were used across these studies, including school bullying behaviors (including relational, verbal, and/or physical violence) among student peers [22,35]; sexual assault incidents that took place in dating or a potential dating relationship [20,21,35,36]; a combination of different types of assaults among friends or acquaintances [30]; and verbal and physical assaults that occurred among strangers [19,29,31,37]. In addition to the victim-aggressor relationship, we examined the relationship between victims and bystanders simulated in the VR scenarios, including school peers (n=2) [22,35], friends (n=5) [20,21,30,36,38], and strangers (n=4) [19,29,31,37].…”
Section: Review Results and Summary Of The Main Characteristics Of Thmentioning
confidence: 99%
“…Different violent incident scenarios were used across these studies, including school bullying behaviors (including relational, verbal, and/or physical violence) among student peers [22,35]; sexual assault incidents that took place in dating or a potential dating relationship [20,21,35,36]; a combination of different types of assaults among friends or acquaintances [30]; and verbal and physical assaults that occurred among strangers [19,29,31,37]. In addition to the victim-aggressor relationship, we examined the relationship between victims and bystanders simulated in the VR scenarios, including school peers (n=2) [22,35], friends (n=5) [20,21,30,36,38], and strangers (n=4) [19,29,31,37]. Regarding study participants, four studies recruited middle or high school students [20,22,35,38], three studies sampled undergraduate students [21,30,36], and the four remaining studies included participants who identified as soccer fans supporting different teams [19,29,31,37].…”
Section: Review Results and Summary Of The Main Characteristics Of Thmentioning
confidence: 99%
“…The relatively low risk of bystander victimization reported in this study is supported by self‐report survey data, showing that between 4% and 18% of bystanders (dependent on incident type) are reportedly threatened or harmed during episodes of interpersonal aggression (Hamby, Weber, Grych, & Banyard, ). In the context of sexual and relationship violence, the likelihood of being physically harmed for intervening, estimated from a university sample, is between 5% and 9% (Krauss et al., ).…”
Section: What Do We Know About the Actual Behavior Of Bystanders In Tmentioning
confidence: 99%
“…It turns out that the real risks are low. Research analyzing real‐life bystander victimization as recorded in CCTV data (Liebst et al., ) and also in self‐report accounts (Hamby et al., ; Krauss et al., ) shows that the risk of physical harm is minimal. Of course, there may be a number of psychological consequences associated with bystander intervention.…”
Section: Rethinking the Bystander Effect In Violence Reduction Programsmentioning
confidence: 99%
“…The TTM asserts that movement toward later stages of readiness is not linear and individuals could relapse or move backward. Based on recent research that students who report a negative intervention experience report diminished intention to intervene in the future (Krauss et al 2017;Witte et al 2017), there is potential for students who have intervened in the past to choose differently in the next opportunity. Banyard and colleagues (2010) hypothesized that RTH precedes bystander behaviors, although the directionality of this assumption was not tested here.…”
Section: Limitations and Future Researchmentioning
confidence: 99%